(untitled) (Baghdad Science Journal, 2012)
In this article the unsteady magnetohydrodynamics oscillating flow of third order fluid with free stream velocity is proposed. It is found that the motion equation is controlled by five dimensionless parameters namely the coecostic parameter 4, viscoelostic parameter ?,acceleration/deceleration c,suction/blowing d and material constants ? . The effect of each of these parameters upon the velocity distribution is analysised